The Complications of Myopia: A Review and Meta-Analysis - Haarman, Annechien E. G.; Enthoven, Clair A.; Tideman, J. Willem L.; Tedja, Milly S.; Verhoeven, Virginie J. M.; Klaver, Caroline C. W. (Investigative ophthalmology & visual science, 2020)
To determine the risk between degree of myopia and myopic macular degeneration (MMD), retinal detachment (RD), cataract, open angle glaucoma (OAG), and blindness. A systematic review and meta-analyses of studies published before June 2019 on myopia complications. Odds ratios (OR) per complication and spherical equivalent (SER) degree (low myopia SER < -0.5 to > -3.00 diopter [D]; moderate myopia SER ≤ -3.00 to > -6.00 D; high myopia SER ≤ -6.00 D) were calculated using fixed and random effects models. Low, moderate, and high myopia were all associated with increased risks of MMD (OR, 13.57, 95% confidence interval [CI], 6.18-29.79; OR, 72.74, 95% CI, 33.18-159.48; OR, 845.08, 95% CI, 230.05-3104.34, respectively); RD (OR, 3.15, 95% CI, 1.92-5.17; OR, 8.74, 95% CI, 7.28-10.50; OR, 12.62, 95% CI, 6.65-23.94, respectively); posterior subcapsular cataract (OR, 1.56, 95% CI, 1.32-1.84; OR, 2.55, 95% CI, 1.98-3.28; OR, 4.55, 95% CI, 2.66-7.75, respectively); nuclear cataract (OR, 1.79, 95% CI, 1.08-2.97; OR, 2.39, 95% CI, 1.03-5.55; OR, 2.87, 95% CI, 1.43-5.73, respectively); and OAG (OR, 1.59, 95% CI, 1.33-1.91; OR, 2.92, 95% CI, 1.89-4.52 for low and moderate/high myopia, respectively). The risk of visual impairment was strongly related to longer axial length, higher myopia degree, and age older than 60 years (OR, 1.71, 95% CI, 1.07-2.74; OR, 5.54, 95% CI, 3.12-9.85; and OR, 87.63, 95% CI, 34.50-222.58 for low, moderate, and high myopia in participants aged >60 years, respectively). Although high myopia carries the highest risk of complications and visual impairment, low and moderate myopia also have considerable risks. These estimates should alert policy makers and health care professionals to make myopia a priority for prevention and treatment.